Long non-coding RNA LINC01480 is activated by Foxo3a and promotes hydroquinone-induced TK6 cell apoptosis by inhibiting the PI3K/AKT pathway - Hui Yang; Yuting Chen; Minjuan Zeng; Haipeng Wu; Xiangli Zou; Tiantian Fang; Lu Zhai; Hairong Liang; Hao Luo; Gaiqin Tian; Qizhan Liu; Huanwen Tang (Ecotoxicology and Environmental Safety, 2023)
Long non-coding RNAs (lncRNAs) have been shown to play a critical role in the damage caused to the body by environmental exogenous chemicals; however, few studies have explored their effects during exposure to benzene and its metabolite, hydroquinone (HQ). An emerging lncRNA, LINC01480, was found to be associated with the immune microenvironment of some cancers, but its specific function remains unknown. Therefore, this study aimed to investigate the role of LINC01480 in HQ-induced apoptosis. The biological function of LINC01480 was investigated through gain-of-function and loss-of-function experiments. Mechanically, nuclear-cytoplasmic fractionation experiment, chromatin immunoprecipitation (ChIP), dual-luciferase reporter assay, and rescue experiments were performed. In this study, when TK6 cells were treated with HQ (0, 5, 10, and 20 μM) for 12, 24, 48, and 72 h, the expression of LINC01480 was increased in a dose-dependent manner. Meanwhile, the phosphorylation levels of PI3K and AKT decreased, and apoptosis increased. As compared to the control group, HQ-induced apoptosis was significantly reduced, and the relative survival rate of TK6 cells increased after silencing LINC01480, while overexpression of LINC01480 further sensitized TK6 cells to HQ-induced apoptotic cell death. LINC01480 negatively regulated the PI3K/AKT pathway in TK6 cells, and the apoptosis-inhibiting effect of LINC01480 silencing was reversed after inhibition of the PI3K/AKT pathway. In addition, ChIP and the dual-luciferase reporter assays showed that the transcription factor Foxo3a promoted LINC01480 transcription by directly binding to the promoter regions − 149 to − 138 of LINC01480. Moreover, short-term HQ exposure promoted the expression of Foxo3a. From these findings, we can conclude that LINC01480 is activated by Foxo3a, and promotes HQ-induced apoptosis by inhibiting the PI3K/AKT pathway, suggesting that LINC01480 might become a possible target for therapeutic intervention of HQ-induced toxicity.